SOSIALISASI PENGENALAN OLAHRAGA CRICKET DI KECAMATAN LEMAHABANG KARAWANG - Basri, Hasan; Azhari, Adli; Putra, Farian Agata (LPPM Universitas Islam 45 Bekasi, 2021)
Cricket is a sport that can be played by all ages and all groups of people, both teenagers and the general public. Currently in Indonesia cricket is in the socialization stage so that the development of cricket is important to promote. The purpose of this community service activity is to provide an overview and practice cricket. The method used is in the form of basic socialization of the introduction of cricket. The result achieved is that the physical education teachers in the Lemahabang sub-district get an understanding and practice it well according to the theory and rules of the game in cricket.